2008
DOI: 10.1029/2008eo370002
|View full text |Cite
|
Sign up to set email alerts
|

Ground Deformation Imagery of the May Sichuan Earthquake

Abstract: The magnitude Mw = 7.8 earthquake that struck China's Sichuan region on 12 May 2008 (Figure 1a) has been imaged by the Italian Space Agency's (ASI) Constellation of Small Satellites for the Mediterranean Basin Observation (COSMO)‐SkyMed radar Earth observation satellites. Five images were available—two preseismic spotlight mode images and three strip‐map mode images, two of which are preseismic and one of which is postseismic. We used two strip‐map images (acquired 1 month prior to and 3 days after the earthqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
1
7
0
Order By: Relevance
“…Finally, from the same figure it can be observed that the DinSAR ground deformations result reported for the vicinity of the Chengdu region is of 0.12 m, which is also of the order of the maximum permanent synthetic displacements values of the synthetics for this town. From these results, we think that the comparisons of the synthetic displacements obtained in this work are in reasonable agreement with the DinSAR results of Ge et al (2008) and Stramondo et al (2008) fig. 3.1 in Yuan and Sun, 2008) is presented in Figure 18.…”
Section: Modeling Resultssupporting
confidence: 88%
“…Finally, from the same figure it can be observed that the DinSAR ground deformations result reported for the vicinity of the Chengdu region is of 0.12 m, which is also of the order of the maximum permanent synthetic displacements values of the synthetics for this town. From these results, we think that the comparisons of the synthetic displacements obtained in this work are in reasonable agreement with the DinSAR results of Ge et al (2008) and Stramondo et al (2008) fig. 3.1 in Yuan and Sun, 2008) is presented in Figure 18.…”
Section: Modeling Resultssupporting
confidence: 88%
“…The phase differences are then calculated and converted into height information, which can clearly indicate surface deformation related to earthquakes [Tronin, 2006]. InSAR has attracted much attention from researchers involved with landslide monitoring and hazard assessment associated with the earthquakes [Stramondo et al, 2008]. Figure 1d show the forest areas devastated by the earthquake (image from Taiwan's space organization (NSPO) Figure 1h represent light scattering from many collapsed buildings.…”
Section: Satellite Monitoring Of Existing Hazardsmentioning
confidence: 99%
“…The phase differences are then calculated and converted into height information, which can clearly indicate surface deformation related to earthquakes [Tronin, 2006]. InSAR has attracted much attention from researchers involved with landslide monitoring and hazard assessment associated with the earthquakes [Stramondo et al, 2008].…”
Section: Better Preparedness Through Better Mapsmentioning
confidence: 99%